AN ANALYSIS OF LANGUAGE STYLE REFLECTING POLITENESS IN QORYGORE’S VIDEO - Maharani, Lutfiana; Fadloeli, Odo (IKIP Siliwangi, 2021)
The purpose of this study is to analyze various styles of language and also politeness in them. The first phase in this project is by watching a video from one of the youtubers named Qorygore. The second phase, records what or what utterances are said on the video. Then in the third phase, it starts analyzing the language style and politeness. During the analysis of the data, the researcher try to find the utterances are related to language style and politeness, and the type of language style found in this result of analysis data are formal and casual style, while the thing that reflects the politeness that is more dominant is negative politeness. Keywords: Language Style, Negative/Positive Politeness